Pistachio production and industry in Turkey: current status and future perspective - Ak B.E.; Karadag S.; Sakar E. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
The pistachio nut belongs to the genus Pistacia of the family Anacardiacea. Pistacia genus have 11 species. Some of the species play an important role in vegetation at the Mediterranean and Asian regions and most of them have proved successful as rootstocks for top working the cultivated pistachio nut. Except Pistacia vera the other species have no economical significance. They are called wild pistachios. In Afghanistan, Iran, Pakistan, Turkey and all the Mediterranean countries there are millions of wild pistachio trees or bushes which belong to different Pistacia species. Pistacia species are grown in 30º-40º latitude and are suited for different climate areas in the world. In Turkey, during last decades new plantations are being established and pistachio farmers conscious of the importance of male tree and irrigation. Nowadays due to governmental support the farmers are applying good agricultural practices rules for their orchards
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)